The Role of Tax Socialization in Mediating Digital Literacy and Taxpayer Trust on Coretax Acceptance - Elfa Nur Sa`ida; Jeni Susyanti; Harun Alrasyid (Almana : Jurnal Manajemen dan Bisnis, 2026)
The coretax system in Indonesia represents a significant change in tax administration, and user acceptance in a mandatory setting is a determinant of its success. This study aims to examine the influence of digital literacy and trust in tax authorities on Coretax system acceptance, with tax socialization effectiveness as a mediating variable. Using a quantitative causal-explanatory design, survey data from 150 individual taxpayers at KPP Pratama Malang Utara were analyzed via PLS-SEM. The findings indicate that digital literacy and trust in tax authorities do not affect coretax system acceptance. Nonetheless, both variables significantly influence tax socialization effectiveness. The most important factor that drives acceptance is tax socialization effectiveness, which enhances the relationship between taxpayer features and system adoption. The conclusion shows that in a mandatory digital environment, skills and trust alone are insufficient. Both have to be activated through the right socialization strategies for a successful implementation into the system.